Multi Dimensional Portrait Method of Industrial Users’ Comprehensive Energy Consumption Index System Under the Background of Carbon Neutrality - Yan SHEN; Dongdong LI; Shunfu LIN (Zhongguo dianli)
As an important subject of energy consumption and carbon dioxide emissions, it is of great importance to portray the comprehensive energy efficiency of industrial users reasonably. Meanwhile, they are the key targets for the realization of the “dual carbon goal”. For this purpose, we establish a multidimensional portrait of industrial users based on the comprehensive energy use index system. Firstly, we construct a corresponding evaluation system from five dimensions: reliable energy use, efficient energy use, economic energy use, low-carbon energy use and intelligent energy use and formed a comprehensive evaluation index system with target layer, criterion layer and index layer. Secondly, we obtain index weights and calculate the integrated energy use index based on hierarchical analysis to form a multidimensional energy use portrait of industrial users. Finally, by selecting four industrial users from different industries as examples, the effectiveness of the proposed method is verified.